ECCLESIA REFORMATA SEMPER REFORMANDA: REFLEKSI BAGI PEMBAHARUAN GEREJA INJILI - Mulyo Kadarmanto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2018)
This paper aims to discuss the principle of ecclesia reformata semper reformanda which is the fruit of the continuation of reform. Through this research literature study will look at the historical background and principles of the slogan, which is expected to be able to find its relevance for the evangelical church in this global era. With an ongoing commitment to renewal in the evangelical church, the evangelical church can again understand its historicity as a doctrinal movement that places the gospel (the Scriptures) as the main foundation for renewal. Recognizing that continuous renewal is a necessity for the evangelical church, will certainly encourage efforts for the evangelical church to maintain purity and vitality, so as to be able to face the present challenges within the framework of the evangelical doctrine as a doctrinal heritage of reform.